Dasometric Valuation and Calculation of the Calorific Value in the wood of the Forest Species Alnus acuminata kunth in the Annex of Pillo, Pampas-Tayacaja, 2024 (GnosisWisdom, 2024)
The article "Dasometric Assessment and Calculation of the Calorific Value in the wood of the Forest Species Alnus acuminata in the Annex of Pillo, Pampas-Tayacaja, 2024" presents a comprehensive study on the wood of Alnus acuminata, known as alder, in the Annex of Pillo, Pampas-Tayacaja. The main objective is to evaluate the dasometric characteristics and determine the calorific value of this forest species. The research aims to provide crucial data for sustainable forest management and efficient timber use. Stratification sampling techniques and dasometric measurements were used to assess tree height, diameter and volume. Calorific value analysis was carried out with a bomb calorimeter, determining the upper calorific value (HCV) and lower calorific value (LHV) of the wood. The results indicate that the PCS of Alnus acuminata is competitive, although slightly lower than other species such as Eucalyptus globulus and Pinus radiata.  As for the lower calorific value, the forest species Alnus acuminata Kunth has a value of 451.455Kcal/kg, as for the upper calorific value it was 990.455 Kcal/Kg, it has a moderate density, a volumetric shrinkage of 7% and a calorific value suitable for energy applications, although with some variations depending on the part of the tree and the moisture content. In conclusion, alder wood is valuable for both forest management and energy harvesting, with important considerations for its management and use in different contexts.
Keywords: Calorific value; Alnus acuminata kunth; dasometric assessment